The Effect of Company Size, Company Age, Auditor's Opinion, and Public Ownership on the Timeliness of Submitting Financial Statements (Empirical Study on Manufacturing Companies Listed on the Idx For the Period 2011 – 2015) - Ratna Dwi Titi Rahayu (ProBisnis : Jurnal Manajemen, 2021)
The purpose of this research is to analyze the effect of Company Size, Company Age, Auditor Opinion, and Public Ownership on Financial Reporting Timeliness of the manufacture company in Indonesia Stock Exchange (IDX) for the period 2011 - 2015. This research type was causal comparative research. Sampling method used purposive sampling. Population of this research is company in manufacture at Indonesian Stock Exchange in 2011, 2012, 2013, 2014, and 2015 with 23 companies as sample. Data that use in this research provide by audited financial report in 2011-2015 that publish in www. idx.co.id. Logistic regression use to test hypothesis. The result of this research show that: (1) Company Size had significant on Financial Reporting Timeliness, as shown by the value of level significant 0.046 < 0.05.